1996
DOI: 10.1073/pnas.93.15.8072
|View full text |Cite
|
Sign up to set email alerts
|

Purification, molecular cloning, and expression of the mammalian sigma1-binding site.

Abstract: Sigma-ligands comprise several chemically unrelated drugs such as haloperidol, pentazocine, and ditolylguanidine, which bind to a family of low molecular mass proteins in the endoplasmic reticulum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
791
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 837 publications
(813 citation statements)
references
References 46 publications
20
791
1
1
Order By: Relevance
“…In the1980s, binding studies by Tsung-Ping Su indicated that σ receptors were new and previously uncharacterized receptors (Su, 1981;Su, 1982). When the receptor was cloned in the 1990s, the results confirmed that its sequence differed from all other known proteins (Hanner et al, 1996). The endogenous ligand for σ receptors has yet to be conclusively determined, although the identity of the receptor protein is now well established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the1980s, binding studies by Tsung-Ping Su indicated that σ receptors were new and previously uncharacterized receptors (Su, 1981;Su, 1982). When the receptor was cloned in the 1990s, the results confirmed that its sequence differed from all other known proteins (Hanner et al, 1996). The endogenous ligand for σ receptors has yet to be conclusively determined, although the identity of the receptor protein is now well established.…”
Section: Introductionmentioning
confidence: 99%
“…The σ-1 subtype has been cloned from various species, such as rat, mouse, and human (Hanner et al, 1996;Seth et al, 1997;Pan et al, 1998;Seth et al, 1998;Mei and Pasternak, 2001). It is a 233 amino acid protein with two putative transmembrane spanning regions (Jbilo et al, 1997;Aydar et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative therapeutic approach to treating cocaine addiction, therefore, would be to target the sigma 1 receptor, which has recently been demonstrated to be involved in cocaine's rewarding effects measured using a conditioned place preference (CPP) paradigm in mice (Romieu et al 2000). The sigma 1 receptor, localized intracellularly within the neurons, is a 223 amino acid protein, cloned in several animal species and humans (Hanner et al 1996;Kekuda et al 1996;Seth et al 1997Seth et al , 1998Pan et al 1998). The receptor appeared devoid of analogy with any other known mammalian protein and its endogenous ligand has still to be established, but its regional and subcellular distributions have recently been determined by immunohistochemical labeling in rodents Phan et al 2000).…”
mentioning
confidence: 99%
“…11 The σ 1 receptor subtype has been purified and cloned from several animal species and man. 12,13 Its primary sequence is now available and shows remarkable homology with sterol C8-C7 isomerase from fungi. The σ 1 receptors exert a modulatory role on neurotransmitter systems such as dopaminergic, serotoninergic, and muscarinic systems 5,14,15 and on the NMDA-stimulated neurotransmitters' release.…”
Section: Introductionmentioning
confidence: 99%